2018
DOI: 10.48550/arxiv.1812.11941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Quality Monocular Depth Estimation via Transfer Learning

Abstract: Accurate depth estimation from images is a fundamental task in many applications including scene understanding and reconstruction. Existing solutions for depth estimation often produce blurry approximations of low resolution. This paper presents a convolutional neural network for computing a high-resolution depth map given a single RGB image with the help of transfer learning. Following a standard encoder-decoder architecture, we leverage features extracted using high performing pre-trained networks when initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
182
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(209 citation statements)
references
References 25 publications
2
182
0
1
Order By: Relevance
“…The best result of supervised learning-based method is shown in red and bold values, the best result of unsupervised learning-based method is shown in blue and bold values, the best result of semi-supervised learning-based method is shown in green and bold values, and the best result of domain adaptation method is shown in cyan and bold values. The results of Saxena et al [36] are reproduce from Eigen et al [20]; the running-time of Fu et al [89] is reported in Patil et al [158]; the running-time of Alhashim et al [86] is reported in Wang et al [113].…”
Section: Monocular Depth Estimation With Domain Adaptationsupporting
confidence: 67%
See 2 more Smart Citations
“…The best result of supervised learning-based method is shown in red and bold values, the best result of unsupervised learning-based method is shown in blue and bold values, the best result of semi-supervised learning-based method is shown in green and bold values, and the best result of domain adaptation method is shown in cyan and bold values. The results of Saxena et al [36] are reproduce from Eigen et al [20]; the running-time of Fu et al [89] is reported in Patil et al [158]; the running-time of Alhashim et al [86] is reported in Wang et al [113].…”
Section: Monocular Depth Estimation With Domain Adaptationsupporting
confidence: 67%
“…The stacked images are fed to an encoderdecoder architecture to learn depth from fused information. Based on DenseNet-169 [83], Alhashim and Wonka [86] design a densely connected encoder-decoder architecture. Unlike [22], they use a simple decoder method which consists of a bilinear upsampling and two convolution layers.…”
Section: A Depth Estimation With Supervised Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Predicting depth from a single image is an ill-posed problem. However, learning based approaches have shown impressive performance by either treating monocular depth estimation as a regression or classification task [1,13,15,16,18,19,22,23,44,45,58,59]. Recent advances include BTS [23], which introduces local planar guidance layers to guide the features to full resolution instead of standard upsampling layers during the decoding phase.…”
Section: Related Workmentioning
confidence: 99%
“…Unlike general depth images from datasets such as NYU [31], the DenseTact dataset requires more focus on the local deformation information since the global information is similar between datasets. Therefore, a much simpler version of the network is selected with a pre-trained encoder and decoder with skip connections [32]. The encoder part of the network consists of a pre-trained DenseNet-161 [33].…”
Section: Modelingmentioning
confidence: 99%